Characterization of the prescription of physical and rehabilitation medicine in health centers in the North of Portugal - Ribeiro, Sandra (2023)
Introduction: Family doctors play a key role in identifying patients in need of and prescribing rehabilitation and physical medicine treatments. Since there is no central record of rehabilitation prescriptions, it is impossible to know the population of patients undergoing rehabilitation. Objectives: Characterizing prescriptions of physical rehabilitation care from four primary care units in the North of Portugal, in 2019. Methods: Observational, analytical, retrospective study of a randomized sample of 400 prescriptions of a first cycle in rehabilitation care, in four primary care units, in 2019. Results: In the analyzed sample, the majority of the patients were female, with an average age of 58 years, an education level equal to or inferior to primary education, and not working at the moment of the prescription. Most prescriptions were due to musculoskeletal complaints (71%), followed by unspecific causes (17%), and the nervous system (5%). From the musculoskeletal motives, 43% were degenerative, 21% inflammatory, and 8% traumatic. From the analyzed initial prescriptions, 61% were not followed by subsequent prescriptions. Conclusions: This study characterizes the patients and the motives that lead physicians of four primary care units to prescribe rehabilitation care. Musculoskeletal diseases were the leading cause of rehabilitation care prescription. The majority of the population had low education and was retired/unemployed despite still being of working age. Most of the initial treatments were not followed by subsequent prescriptions. This study can be a starting point for future investigations and practice improvements in this care area.